2008
DOI: 10.1002/anie.200704683
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crystallography through Supramolecular Interactions between a Lanthanide Complex and Arginine

Abstract: The determination of the complete sequence of the human genome triggered the emergence of structural proteomics, a challenging field of research devoted to the determination of the structure of proteins at atomic resolution to understand their structure-function relationships. Among the various techniques for structure determination, [1] X-ray crystallography plays an essential role. Its bottleneck is the serendipitous and time-consuming preparation of well-diffracting crystals. Once such crystals are obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…[14] It has been reported that [Ln(dpa) 3 ] 3À complexes can be fixed on the protein through hydrogen bonds between the oxygen atomso ft he carboxylate groups of dpa and the protein hydrogen-bond donors such as the amino groups. [15] The resulting hybrid composites are highly soluble in water,d isplaying improveds tability and prolonged lifetimei nc omparison with the pure complex, and they also presenthighly selective and sensitive sensing for Cu 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…[14] It has been reported that [Ln(dpa) 3 ] 3À complexes can be fixed on the protein through hydrogen bonds between the oxygen atomso ft he carboxylate groups of dpa and the protein hydrogen-bond donors such as the amino groups. [15] The resulting hybrid composites are highly soluble in water,d isplaying improveds tability and prolonged lifetimei nc omparison with the pure complex, and they also presenthighly selective and sensitive sensing for Cu 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Finally following pioneering workso fK ahn andc o-workers in the early 2000s, it is possiblet oi ncorporate lanthanide complexesi nto bio-macromolecules via an etwork of non-covalent interactions for X-rays crystallography structure determination. [8] This methodi sv ery simple and easy to perform but is less predictable since the study of lanthanide complexes-protein interactions is an almoste mptyf ield of research [9] In this context,w ed escribed the use of tris-dipicolinate lanthanide complexes ([Ln(DPA) 3 ] 3À ,D PA = 2,6-pyridine dicarboxylate; Figure1)t hat are ablet oc o-crystallize efficiently with al arge number of proteins [10] andw ee videnced ap articulara ffinity of this complexf or cationic amino acids according to the sequence arginine > histidine > lysine. [11] The groups of Otting and Su have also used these complexes to determine the structure of the proteins ArgN andu biquitin in solution by NMR.…”
Section: Introductionmentioning
confidence: 99%
“…However, incorporation of lanthanides by using lanthanide salts often damages protein crystals, owing to the preferred nine-based coordination of lanthanide ions. One solution to overcome this problem is to use lanthanide complexes made of a ligand that surrounds the lanthanide ions as a cage [14,15]. These complexes can be easily introduced in protein crystals and turn out to be efficient vehicles for phasing using anomalous dispersion, in particular for large macromolecular assemblies (for a short overview of protein structures determined using these lanthanide complexes, see [13]).…”
Section: Instrumentation and Milestonesmentioning
confidence: 99%